2020
DOI: 10.1002/cbf.3597
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between vitamin D status, SARS‐CoV‐2 infection risk and COVID‐19 severity?

Abstract: The outbreak of COVID‐19 emerged in December 2019 rapidly spread across the globe and has become pandemic. Little is known about the protective factors of this infection, which is equally distributed between genders and different ages while severe and poor prognosis cases are strongly associated to old males and the presence of comorbidities. Thus, preventive measures aiming at reducing the number of infection and/or their severity are strongly needed. Vitamin D has got great attention and has been claimed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 189 publications
(204 reference statements)
0
30
0
1
Order By: Relevance
“… 19 , 20 A narrative review aimed at collecting the literature available on involvement of vitamin D status in the pathogenesis of COVID-19 and the putative utility of vitamin D supplementation in therapeutics concluded that poor vitamin D status seems to be associated with an increased risk of infection, whereas age, sex, and comorbidities seemed to play a more important role in COVID-19 severity and mortality. 21 There is a need to generalize and summarize the findings of individual studies to synthesize evidence that helps make COVID-19 prevention effective. Therefore, the purpose of this study was to undertake a systematic review to summarize and determine whether there is a relation between vitamin D status and COVID-19 infection and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 A narrative review aimed at collecting the literature available on involvement of vitamin D status in the pathogenesis of COVID-19 and the putative utility of vitamin D supplementation in therapeutics concluded that poor vitamin D status seems to be associated with an increased risk of infection, whereas age, sex, and comorbidities seemed to play a more important role in COVID-19 severity and mortality. 21 There is a need to generalize and summarize the findings of individual studies to synthesize evidence that helps make COVID-19 prevention effective. Therefore, the purpose of this study was to undertake a systematic review to summarize and determine whether there is a relation between vitamin D status and COVID-19 infection and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…26 A role that Schools of Public Health must undertake is to evaluate proposed interventions in light of conflicting evidence. 27,28…”
Section: Nutritionmentioning
confidence: 99%
“…As very recently reviewed, in addition to its classical hormone action related to calcium homeostasis and bone metabolism, vitamin D is supposed to be more or less directly involved in a plethora of physiological mechanisms aimed at maintaining the whole-body homeostasis. For example, in recent years, vitamin D has emerged as a potential immune modulator [2]. The most active metabolite of the vitamers D, 1α,25-(OH) 2 D [3], regulates development, maturation, and functioning of different lineages of immune cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have evidenced the association and sometimes, a causal link between hypovitaminosis D status and both the risk of SARS-CoV-2 infection and the severity and mortality of COVID-19 [2]. However, since the different approaches applied and the great differences in the cohorts studied, these associations have not always been confirmed [21].…”
Section: Introductionmentioning
confidence: 99%